2007
DOI: 10.1007/s11605-007-0369-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Anastomotic Complications After Pancreaticoduodenectomy for Benign Diseases

Abstract: Intervention for anastomotic strictures after pancreaticoduodenectomy is uncommon. Biliary strictures can usually be treated nonoperatively with dilation and stent. Our study likely underestimates the incidence of stricture formation. Prospective imaging studies may be warranted for a more accurate assessment of the rate of long-term anastomotic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
90
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 23 publications
(21 reference statements)
5
90
1
Order By: Relevance
“…There is evidence that preoperative biliary drainage increases the incidence of septic complications. 7,13 Endoscopic biliary stenting (as opposed to percutaneous biliary drainage) has also been reported to be protective. 3 Younger patients with injury and benign disease usually have non-dilated bile ducts and are less likely to have received preoperative biliary drainage than those undergoing surgery for malignancy (53% versus 67%).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that preoperative biliary drainage increases the incidence of septic complications. 7,13 Endoscopic biliary stenting (as opposed to percutaneous biliary drainage) has also been reported to be protective. 3 Younger patients with injury and benign disease usually have non-dilated bile ducts and are less likely to have received preoperative biliary drainage than those undergoing surgery for malignancy (53% versus 67%).…”
Section: Discussionmentioning
confidence: 99%
“…Though low mortality at high-volume medical centers has been achieved (Ho and Heslin, 2003), PDs are still associated with high postoperative morbidity and exo-and endocrine dysfunction (Ghaneh and Neoptolemos, 1999;Grobmyer et al, 2007;Tran et al, 2009). Long-term biliary and pancreatic anastomotic complications following PDs have also been noted (Reid-Lombardo et al, 2007). The amount of resected pancreatic parenchyma largely affects postoperative quality of life of the patients, especially for young patients with a long life expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…Besides pancreatic parenchyma, the integrated upper digestive and biliary anatomy also plays a key role in maintaining consequent digestive, immunological and coagulative function and neurohormonal regulation of insulin activity [15] . In addition, ReidLombardo et al [16] have reported that the 5 and 10year cumulative probability of biliary stricture after PD for benign lesions was 8% and 13%; that is why, in recent years, CR, such as central pancreatectomy and enucleation, has been investigated with great interest. In the present study, with a mean of 42.7 mo followup, there was no newonset diabetes mellitus and pancreatic exocrine insufficiency, which is the same as previously reported [1723] .…”
Section: Discussionmentioning
confidence: 99%